On test oracles for Simulink-like models - Nardi, Paulo Augusto (2013)
Embedded systems are present in many fields of application where failure may be critical. Such systems often possess characteristics that hampers the testing activity, as large amount of produced data and temporal requirements which must be specified and evaluated. There are tools that support the development of models for analysis and simulation still in the design stage. After being evaluated, a model may be used as basis to the implementation. In this case, it is important to ensure that the model is consistent with the specification. Otherwise, a divergence will be propagated to the final code. Therefore, the model must be tested prior to the codification. Simulink is a standard development and simulation tool for models of embedded systems. Its wide application in the industry has promoted the creation of free-software alternatives, as XCos. In the literature, there are researches which seek to improve the testing activity for Simulink-like models. The proposed solutions usually focus on test case selection strategies. However, little efforts have been directed to the oracle problem, that is, the difficulty in evaluating if an execution agrees with the specification. The objective of this doctorate proposal is to provide an oracle generation approach for Simulink-like models which addresses the characteristics previously summarized. Specifically, it is proposed a process, methods, procedures and a tool that enable the partially-automated generation of oracles for such models. As a main contribution, it is expected an improvement in the evaluation process of embedded systems in terms of quality, cost and time